AUSES OF MORAL DECAY AMONG YOUTH IN ST JAMES PARISH IN BUSOGA DIOCESE - Kifuuse Fredrick (Ucu, 2024)
This study aimed at examining the causes of moral decay in St. James Parish Church, Jinja Archdeaconry, BusogaDiocese. The study was guided by the following objectives: determining the causes of moral decadence among youth in St James Parish Church, establishing the effects of moral decay among youth in St James Parish Church and establishing what could be done to curb moral decay among youth in St James Parish Church in Busoga Diocese. The study was conducted usingboth qualitative and quantitative research approaches. Data was collected using self-administered questionnaires from the selected youth, parents and religion leaders from St. James Parish Church, Iganga, Busoga Diocesetotaling to 50 who were selected using simple random sampling method. The study findings revealed that moral decadence among youth in St. James Parish Church is primarily driven by poor parental guidance (94%), the negative impact of technology (96%), and significant peer influence (96%). Additionally, excessive freedom and developmental challenges hinder moral reasoning. The community emphasizes the need for increased parental involvement and the implementation of targeted interventions, such as enhanced Bible study and guidance programs, to promote moral values. There is also a call for maintaining a balance between religious and moral education in the curriculum, alongside advocating for the autonomy of religious organizations to effectively instill moral discipline. Finally, thestudy recommended the need for enhanced parental involvement in the moral education of youth. The study also recommends the need for the establishment of technology use guidelines within both home and church settings and the need for the church to implement guidance and counseling programs aimed at youth. Lastly, the study recommends the need for maintaining religious education alongside moral education in the curriculum of local schools.